O controle social da gestão dos recursos públicos para educação: um estudo a partir do conselho do fundeb em mossoró/rn - Marques, Thiago Henrique Gomes Duarte (2019)
After the enactment of the Federal Constitution of 1988, the participation of society in state actions began to receive greater support, becoming institutionalized in several areas. In the sphere of public resources for basic education, the Fundeb Council is composed of members of society and the State, with the main function of keeping a social control over the use of these resources. Hypothetically, the composition of the Council must guarantee full legitimate representativeness of its base and act in strict accordance with the law making use of all the prerogatives that have been attributed to it. Using content analysis and non-participant observation, applying forms to counselors, and also, analyzing academic papers and laws related to the subject, apart from internal documents of the institution: its internal regulations and minutes, always connected with the appropriate theoretical reference, the conclusion was that the Fundeb Council of Mossoró does not act effectively, not fulfilling about half of its attributions, since the documents presented by the Executive Power for accountability is unintelligible for almost all Counselors, which prevents the effective exercise of social control. All things considered, due to most of the Council's members comes from society, it was concluded that there is no real legitimacy of the Counselors to perform their function, which is observed in particular by the lack of democracy in the choice of the representatives, what is emphasized by the lack of interest by the represented and enhances the lack of dialogue between representatives and represented